The Effect of Employee Background Fit on Employee Retention in the Manufacturing Industry - Hisyam Pratama Islam; Muhammad Donal Mon; Agustinus Setyawan (Cakrawala Repositori IMWI)
Employee retention remains a persistent challenge in the manufacturing sector, where high turnover rates can generate substantial costs and operational inefficiencies that undermine organizational performance. This study aimed to analyze the effect of employee background fit on employee retention while examining the mediating roles of compensation and job satisfaction in this relationship. Data were collected through online questionnaires distributed to 118 employees in technical specialist positions across various manufacturing companies. The proposed model was tested using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4, enabling the analysis of both direct and indirect effects. The findings showed that employee background fit did not have a significant direct effect on employee retention. However, it had a significant indirect effect through compensation, highlighting the important role of equitable remuneration in supporting retention. By contrast, job satisfaction did not significantly mediate the relationship between employee background fit and retention, suggesting that other workplace factors may play a more influential role in this context. These findings challenge the assumption that aligning employees’ expertise and backgrounds with job requirements is sufficient to ensure long-term retention. Instead, they indicate that compensation should be appropriately aligned with employees’ qualifications, expertise, and job demands to strengthen retention, particularly among highly skilled technical employees. The study provides practical implications for human resource practitioners in the manufacturing industry by emphasizing the importance of integrating equitable compensation policies with appropriate job placement to retain a skilled and committed workforce. By clarifying the relationship among employee background fit, compensation, job satisfaction, and retention, this study contributes to the literature on employee retention in industrial settings.